Wireless image transmission network: 3D modelling based on 2D hand drawing with sustainable computing. (15th November 2021) - Li, Hanxiao
Nowadays, we can describe the world in a variety of ways, such as the original text description form, and then to the voice, image, video and other multimedia forms. All these make the methods of describing the world more and more abundant. The appearance of 3D model and 3D scene extends the way of describing the world to 3D space. Because it is closer to the real world, our perception is more rich and more realistic. In the two-dimensional art creation, it is the basic operation mode for art personnel to input and draw two-dimensional images by the handwriting pad. This way is close to manual drawing, in line with the operating habits of artists. In recent years, the emerging research on computational sustainability has become an effective way and a new research hotspot of image wireless transmission. The advent of big data era brings opportunities for the research of computational sustainability, as well as new challenges such as problem complexity, computational efficiency, and method scalability. Based on this background, this paper designs the 3D modelling of 2D hand drawn wireless image transmission network based on sustainable computing model.